Saturday, June 19, 2010

how to prove it - ch5, sec5.2(One-to-one and Onto) ex

This section talks about definition of a one-to-one and/or onto function. The logic formulae for them are used to prove whether a function is one-to-one and/or onto.

One-To-One:
A function f:A -> B is called one-to-one if ¬a1Aa2A(f(a1)=f(a2)a1a2). That is, there don't exists two different elements in A whose value of f is same.
Its easy to see that positive version of above formula(which is used more for proofs) is a1Aa2A(f(a1)=f(a2)a1=a2)

Onto:
A function f:A -> B is called onto if bBaA(f(a)=b) or that every element b in B has some element a in A s.t. (a,b)f. That means, Ran(f) = B.

One-to-One functions are also called injections and Onto functions are also called surjections. The functions that are both one-to-one and onto are called one-to-one correspondence or bijections.

===========================================================================================

Ex-1:
(a) Its not One-to-one as f(1) = f(2) = f(3). It is Onto.
(b) not a function
(c) It is one-to-one but not onto


Ex-2:
(a) Not a function
(b) g is not one-to-one as (ab,a) and (ac,a) both are in g. However, g is onto.
(c) Its both one-to-one and onto.


Ex-3:
(a) Its not one-to-one as f(a) = f(b). However, it is onto.
(b) Its not one-to-one as f(0) = f(2) = 0. It is not onto either as proven below.
We'll prove it by contradiction. Assume its onto. Let c be arbitrary real number. Then we can choose a real number x s.t.
x2-2x=c
=> x2-2x-c=0

For this quadratic equation, D = (4 + 4c), which is negative for any c < -1, Hence no real roots possible if c < 1, which is a contradiction and the function is not onto.
(c) Its not one-to-one as f(2.1) = f(2.2) = 2. However, it is onto.


Ex-4:
(a) It is one-to-one but not onto as there are many cities which are not capital of any nation.
(b) It is both one-to-one and onto.
(c) It is also both one-to-one and onto.


Ex-5:
(a) Prove that f is one-to-one.
Let x,y be arbitrary elements of A s.t. f(x) = f(y).
=> x+1x-1=y+1y-1
=> (x+1)+(x-1)(x+1)-(x-1)=(y+1)+(y-1)(y+1)-(y-1)
=> x = y

So, If f(x) = f(y) then x = y. Since x and y are arbitrary, so f is one-to-one.

Prove that f is onto.
Scratchwork: For any arbitrary b in A, we want to find out an a in A s.t. f(a) = b
=> a+1a-1=b
=> (a+1)+(a-1)(a+1)-(a-1)=b+1b-1
=> a=b+1b-1

Formal Proof: Let b be an arbitrary element of A. Let us choose x = b+1b-1.
Then f(x)
= b+1b-1+1b+1b-1-1
= 2b2
= b

Since b is arbitrary, so f is Onto.

(b) () Let (x,y) be an arbtirary element in ff.
So, y =(ff)(x)
= f(f(x))
= f(x+1x-1)
= x+1x-1+1x+1x-1-1
= x

So, y = x. Then (x,y)iA.

() Let (x,x) be an arbitrary element of ia. Since (ff)(x) = x, so (x,x)ff. Since x is arbitrary, so iAff.

Hence ff=iA


Ex-6:
(a) f(2) = {yRy2<2}
(b) It is ont-to-one but not onto, for example There does not exist any real number s.t. f(x) = {1,2,3}


Ex-7:
(a) f({{1,2},{3,4}}) = {1,2} {3,4} = {1,2,3,4}
(b) It is not one-to-one because f({{1,2},{3}}) = f({{1},{2,3}}) = {1,2,3}. However, it is onto.


Ex-8:
(a) Suppose gf is onto. Let c be an arbitrary element of C, then we can choose some aA s.t. (gf)(a)=c. Then g(f(a)) = c. Let f(a) = b, then g(b) = c. So, for any arbitrary cC we can choose bB s.t. g(b) = c. Hence g is onto.

(b) Suppose gf is one-to-one. Let x and y be arbitrary elements of A s.t. f(x) = f(y) = u.
Now (gf)(x) = g(f(x)) = g(u)
Also (gf)(y) = g(f(y)) = g(u)

Since gf is one-to-one, so x = y. Since x and y are arbitrary, so f is one-to-one.


Ex-9:
(a) Suppose f is onto and g is not one-to-one.
Since g is not one-to-one, so we can choose some b1 and b2 in B s.t. g(b1)=g(b2) but b1b2. Since f is onto, so we can choose a1 and a2 in A s.t. f(a1)=b1 and f(a2)=b2 and a1a2. Thus (gf)(a1) = (gf)(a2) and a1a2. Thus gf is not one-to-one

(b) Suppose f is not onto and g is one-to-one. We will prove by contradiction that gf is not onto. Assume gf is onto.
Since f is not onto, so we can choose a bB s.t. there is no aA s.t. f(a) = b. Let g(b) = c. Since gf is onto, we can choose some aA s.t. (gf)(a)=c. Then g(f(a)) = c. But such a is not possible. This is a contradiction. Hence gf is not onto.


Ex-10: Note: In this exercise f|C denotes the restriction of f to C.
(a) Suppose f is one-to-one. Let c and d be arbitrary elements of C s.t. (f|C)(c) = (f|C)(d) = b, where b is some element of B. Since, CA, so c and d are elements of A also. Then f(c) = b and f(d) = b. Since f is one-to-one so c = d. Since c and d are arbitrary, so If f is one-to-one, then so is f|C.

(b) Suppose f|C is onto. Let b be arbitrary element of B. Since f|C is onto, so we can choose some c in C s.t. (f|C)(c) = b. Then f(c) = b. Since c is arbitrary, so If f|C is onto, then so is f.

(c) Let A = B = R and C = R+. For (a), use f(x) = |x| and for (b) use f(x) = x


Ex-11:
(a) Suppose A has more than one element. Then we can find two different arbitrary elements x and y in A s.t. xy. Since f(x) = f(y) = b, so f is not one-to-one.

(b) Suppose B has more than one element. Then we can choose another element cB s.t. bc. Then there does not exist any xA s.t. f(x) = c. Hence f is not onto.


Ex-12: () Suppose fg is one-to-one. We will prove it by contradiction that Ran(f) and Ran(g) are disjoint. Assume Ran(f) and Ran(g) are not disjoint. Then we can choose some cC s.t. there exist aA and bB s.t. f(a) = c and g(b) = c. Then (fg)(a)=(fg)(b)=c. But fg is one-to-one, so this is contradiction. Hence Ran(f) and Ran(g) are disjoint.
() Suppose Ran(f) and Ran(g) are disjoint. Let x and y be arbitrary elements of AB s.t. (fg)(x)=(fg)(y)=c, where cC. Then either (x,c)f or (x,c)g and either (y,c)f or (y,c)g. Let us consider all the cases

Case#1: (x,c)f and (y,c)f
Since f is one-to-one, so x = y

Case#2: (x,c)g and (y,c)g.
Since g is one-to-one so x = y

Case#3: (x,c)f and (y,c)g
Since Ran(f) and Ran(g) are not disjoint, so this case is not possible

Case#4: (x,c)g and (y,c)f
Since Ran(f) and Ran(g) are not disjoint, so this case is not possible

From all these cases, it is clear that x = y. Since x and y are arbitrary, so f is one-to-one.

Hence, fg is one-to-one iff Ran(f) and Ran(g) are disjoint.


Ex-13: Suppose S is one-to-one.

First, we prove that for every aA, there exists atleast one bB s.t. (a,b)R.
Let a be arbitrary element of A. Since SR is a function, so there exists unique cC s.t. (a,c)SR. Then we can choose some bB s.t. (b,c)S and (a,b)R.

Second, we prove that such a bB is unique.
Let there exists another element dB s.t. (a,d)R. Since Ran(R) = Dom(S) = B, so we can choose some c0C s.t. (d,c0)S. Then (a,c0)SR. Since SR is a function and (a,c)SR and (a,c0)S, so c=c0. Then (d,c)S and (b,c)S. Since S is one-to-one, so b = d. Hence b is unique.

Hence If S is one-to-one, then R: A -> B


Ex-14:
(a) Suppose R is reflexive and f is onto. Let b be an arbitrary element of B. Since f is onto, so we can choose some aA s.t. f(a) = b. Since R is reflexive, so (a,a)R and hence (b,b)S. Since b is arbitrary, so S is reflexive on B.

(b) Suppose R is transitive and f is one-to-one. Let (x,y) and (y,z) be arbitrary elements of S. So there exist unique(unique because f is function) u,v and w s.t. f(u) = x, f(v) = y, f(w) = z and (u,v)R, (v,w)R. Since R is transitive, so (u.w)R. Then (x,z)S. Since (x,y) and (y,z) are arbitrary, so S is transitive.


Ex-15:
(a) Let X be arbitrary element of A/R, so we can choose some xA s.t. X = [x]R. Then g(x) = X. Since X is arbitrary, so g is onto
(b) () Suppose g is one-to-one. Since R is equivalence relation and hence reflexive, so iAR.
Let (x,y) be arbitrary element of R. Then y = [x]R.. Then g(x) = [x]R = g(y). But g is one-to-one, so x = y. Hence RiA.
Thus R = iA

() Suppose R = iA. Let x,y be arbitrary elements of A s.t. g(x) = g(y). Then [x]R=[y]R. Then y[x]R. Then (y,x)R. Then x = y and hence g is one-to-one

So g is one-to-one iff R = iA


Ex-16: () Suppose h is one-to-one. Let x,y be arbitrary elements of A s.t. f(x) = f(y). Then h([x]R) = h([y]R). Since h is one-to-one so [x]R=[y]R. Then xRy
() Suppose xAyA(f(x)=f(y)x=y). Let [x]R, [y]R are arbitrary elements of A/R s.t. h([x]R) = h([y]R). Then f(x) = f(y). Then xRy and then [x]R=[y]R.

Hence h is one-to-one iff xAyA(f(x)=f(y)x=y)


Ex-17: Suppose f is onto, g:B -> C , h:B -> C and gf = hf.
(a) () Let (b,c) be arbitrary element in g. Since f is onto so we can choose aA s.t. f(a) = b. So (a,c)gf. Then (a,c)hf. Then (b,c)h. Hence gh
() Using a similar argument, we can prove that hg.
Hence h = g

(b) [this one is copied from solutions given in the book]
Let c1 and c2 be two distinct elements of C. Suppose bB. Let g and h be functions from B to C s.t. xB(g(x)=c1), xB\{b}(h(x)=c1) and h(b) = c2. Then gh, so gfhf and therefore we can choose some aA s.t. g(f(a)) h(f(a)). But by definition of g and h, there is only one xB s.t. g(x) h(x) is x = b, so it follows that f(a) = b. Since b was arbitrary, so f is onto.


Ex-18:
(a) Suppose f is one-to-one, g:A -> B, h:A -> B and fg=fh.
() Let (a,b) be arbitrary element of g. So we can choose cC s.t. (b,c)f. Then (a,c)fg. Then (a,c)fh. Then we can choose a b0B s.t. (a,b0)f. Since f is one-to-one, so b=b0. Hence (a,b)h. Thus gh.
() Using a similar argument, hg.

Thus g = h.

(b) Let b1 and b2 be arbitrary elements of B s.t. f(b1) = f(b2). Let us define g,h s.t. xA(g(x)=b1) and xA(h(x)=b2).
Now for every xA, (fg)(x) = f(g(x)) = f(b1) = f(b2) = f(h(x)) = (fh)(x). Thus fg = fh. Then g = h. Then for any xA, g(x) = h(x) and hence b1 = b2. Since b1 and b2 are arbitrary, so f is one-to-one.


Ex-19:
(a) Proof for hRf:
Consider j: R -> R defined as j(x) = (x-1)2+1

Let x be an arbitrary real number, then (jf)(x) = j(f(x)) = j(x2+1) = x4+1 = h(x). Since x is arbitrary, so h = jf. Hence hRf.

Proof for gRf is not true:
We will prove it by contradiction. Assume we can choose a function jF s.t. g = jf. Let x be an arbitrary real number. Then, g(x) = (jf)(x)
=> x3+1 = j(x2+1)
=> j(x) = x-13+1

But then j is undefined for anything less than 1 and then jF, which is a contradiction. Hence such a function can't exist and hence gRf is not true.

(b) First, we prove that R is reflexive.
Let f be an arbitrary function in F. Let x be an arbitrary real number. Then (iRf)(x) = iR(f(x)) = f(x). Since x is arbitrary, so f = iRf. Thus fRf. Since f is arbitrary, so R is reflexive on F.

Second, we prove that R is transitive.
Let (f,g) and (g,h) be arbitrary elements of R. Then we can choose two functions j1 and j2 s.t. f = j1g and g = j2h. Let x be arbitrary real number. Then (j1g)(x) = j1(g(x)) = j1(j2(h(x))) = (j1j2)(h(x)). Let j = j1j2. Then (j1g)(x) = (jh)(x). Since x is arbitrary, so f = jh. Thus fRh. So R is transitive.

Hence R is preorder.

(c) Let f be an arbitrary function in F. Let x be an arbitrary real number. (fiR)(x) = f(iR(x)) = f(x). Since x is arbitrary, so f = fiR. So (f,iR)R.

(d) Suppose f is arbitrary function in F.
() Suppose iRRf. Then we can choose jF s.t. iR=jf. Let x and y be arbitrary real numbers s.t. f(x) = f(y).
Then x = iR(x) = (jf)(x) = j(f(x)) = j(f(y)) = (jf)(y) = iR(y) = y. Thus x = y and hence f is one-to-one.

() Suppose f is one-to-one. Let A = Ran(f) and h = f-1((R\A)X{0}).
Proof for h:R -> R :
Existence And Uniqueness: Let x be an arbitrary real number. Let us consider following exhaustive set of cases.

Case#1: xA
Then we can choose a unique(unique because f is one-to-one) real number y s.t. f(y) = x. Then (y,x)f. Then (x,y)f-1. Then (x,y)h. So h(x) = y.

Case#2: xA
Then xR\A. Then (x,0)((R\A)X{0}). Then (x,0)h. So h(x) = 0

hence h is a function from R to R.

Proof for iR=hf:
Let x be an arbitrary real number. Then (hf)(x) = h(f(x)) = x = iR(x). Since x is arbitrary, so iR=hf

Hence iRRf

(e) Let f be an arbitrary element in F. Using result of Ex.14(a) of section 5.1, g = gf. Hence gRf.

(f) Suppose g is a constant function, then we can choose a real number c s.t. for every real number x, g(x) = c.

() Suppose fF(fRg). Then we can choose some function j s.t. f = jg. Let x be an arbitrary real number. Then f(x) = (jg)(x) = j(g(x)) = j(c) = constant. Hence f is a constant function.

() Suppose f is a constant function. Then there is some real number d s.t. for every real number x, f(x) = d. Let us define a function j s.t. j(c) = d. Let x be an arbitrary real number. Then (jg)(x) = j(g(x)) = j(c) = d = f(x). Since x is arbitrary so f = jg. Hence fRg.

(g) Proof for ": set of all one-to-one functions from R to R is the largest element of F/S ":
Let [g]S be the set of all one-to-one functions in F. Using result of part(d), we know that iRRg. Hence we can choose a j1F s.t. iR=j1g.
Let f be an arbitrary function in F. Then using result of part(c) fRiR. Then we can choose a function j2F s.t. f=j2iR. Let us define a function h = j2j1. Let x be an arbitrary real number.
Then (hg)(x)
= h(g(x))
= (j2j1)(g(x))
= j2(j1(g(x)))
= j2((j1g)(x))
= j2(iR(x))
= (j2iR)(x)
= f(x)

Thus f = hg. Hence fRg. And, so [f]ST[g]S. Since f is arbitrary so fF([f]ST[g]S), where [g]S is set of all one-to-one functions in F. Hence Set of all one-to-one functions in F is the largest element of F/S in T.

Proof for ": set of all constant functions from R to R is the smallest element of F/S ":
Let g be a constant function and f be an arbitrary function in F. Using the result of part(e) gRf. Then [g]ST[f]S. Hence set of all constant functions is smallest element of F/S

2 comments:

  1. Hi, I am a college student and I really appreciate your blog! I do have a question regarding exercise 4.a. There are numerous countries with multiple capital cities so would that still make it one-to-one?

    ReplyDelete
    Replies
    1. You may be right in general. However, question kind of assumes that one country can have only one city as its capital or else "H: N -> C" wouldn't be a "function" as said in ex4(a) in section 5.1 .

      Delete